Metode Waterfall pada Sistem Informasi Akademik SMPIT Boarding School Thariq Bin Ziyad Cikarang - Tri Haryati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2019)
The development of web-based information technology is currently increasingly high. One of them is a website. Website has advantages where all the desired information can be easily and cheaply obtained. SMPIT (Boarding School) Thariq bin Ziyad Cikarang - Bekasi, currently processing academic data, especially in value processing is still very simple, namely only with Microsoft Excel. The web-based academic information system is expected to help teachers and students get around academic information more quickly and easily. The development of this academic information system the author uses the waterfall methodology. The design and implementation is done using the PHP programming languages ​​and the database used by PhpMyAdmin. With this academic information system, hopefully it can help to support school performance, especially in academic data processing